THE USE OF DISTRACTION TECHNIQUES FOR PAIN MANAGEMENT IN PEDIATRIC PATIENTS - Ibrahim Mohammed Al Sharif , Munif Amer Munif Aldawsari, Yousef Mohammad Alothman, Hassan Abdullah Alhilal,Rayhanah Tagi Alhelal, Muhammad Abdellatif Al Nasser, Baha Ali Hassan Al Bagshi, Yazeed Saad Al Majed, Hussain Jassim Alahmed, ,; Bilal Salim Almushrife, Ahmed Radi Alahmed,Saleh Ali Bunimah, Ali Abdulhadi Alswuaiq,Abdullhadi Mohammed Almohammed Saleh,Talal Radhi Al Enazi,Hussein Ali Ahmed Alsaleem, (Chelonian Research Foundation, 2022)
Diagnostic testing and treatment regimens for pediatric malignancies may require intrusive and unpleasant procedures. The therapy of severe pain is typically inadequate in many regions worldwide, mostly due to the high cost and restricted accessibility of suitable drugs. Existing research indicates that distraction, which is a cost-effective strategy, has promise as an intervention for managing procedural pain. Nevertheless, there is little data to substantiate its efficacy in pediatric oncology patients. An evaluation was carried out to determine the efficacy of distraction as a procedural pain control method in pediatric cancer patients. A thorough search approach was used to search electronic databases such as MEDLINE, PsycINFO, Cochrane Library, AMED, CINAHL, Web of Science, and EMBASE for papers that compared distraction strategies to standard treatment or any other intervention. A comprehensive review and meta-analysis of randomized controlled trials was done using the chosen papers. This comprehensive review provides evidence that distraction is an effective technique for reducing procedural discomfort. Subsequent studies should evaluate the efficacy of diversion techniques in many groups, in order to investigate the impact of cultural factors on the manifestation, evaluation, and treatment methods of pain. Keywords: Distraction, procedure pain, pediatric patients, cancer, pediatric oncology.